2014
DOI: 10.3109/14647273.2014.956811
|View full text |Cite
|
Sign up to set email alerts
|

Circulating microRNAs in patients with polycystic ovary syndrome

Abstract: We report a novel non-invasive miRNA profile which distinguishes PCOS patients from healthy controls. The miRNA-target database may provide a novel understanding of PCOS and potential therapeutic targets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 39 publications
4
49
1
4
Order By: Relevance
“…Statistically significant inverse relationship between androstenedione concentrations and expression of miR-29a and miR-155 and between 17-OHPg and miR-155 (Figure 1(A-C); S5) is reported. Ding et al [37] showed that miR-29a-3p was downregulated in PCOS patients. In our experimental setting, we report a statistically significant inverse relationship between androstenedione concentrations and expression of miR-29a ( Figure 1(B); S5).…”
Section: Discussionmentioning
confidence: 99%
“…Statistically significant inverse relationship between androstenedione concentrations and expression of miR-29a and miR-155 and between 17-OHPg and miR-155 (Figure 1(A-C); S5) is reported. Ding et al [37] showed that miR-29a-3p was downregulated in PCOS patients. In our experimental setting, we report a statistically significant inverse relationship between androstenedione concentrations and expression of miR-29a ( Figure 1(B); S5).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying mechanisms resulting in PCOS have to this point been elusive; thus, multiple groups have worked towards the identifi cation of miRNA associated with PCOS (Sorensen et al 2014 ). Using microarray and quantitative PCR, fi ve (let-7i-3 pm, miR-5706, miR-4463, miR-3665, miR-638) miRNAs were found in greater abundance in circulation of women with PCOS compared to healthy controls, while four (miR-124-3p, miR-128, miR29a-3p, let-7c) were less abundant in women with PCOS (Ding et al 2014 ). Others have taken similar approaches in the comparison of global miRNA expression profi ling in women with PCOS compared to healthy controls.…”
Section: Polycystic Ovarian Syndromementioning
confidence: 99%
“…De la même maniè re, ils trouvent un inté rêt grandissant dans le domaine de la fertilité , dans le but d'amé liorer la prise en charge des couples infertiles. Ainsi, chez la femme, ils ont dé jà dé montré leur efficacité à identifier certaines pathologies de la ré serve ovarienne [15][16][17][18][19][20][21], à é valuer la qualité du microenvironnement folliculaire [22] et à pré dire le dé veloppement embryonnaire in vitro, lors d'une prise en charge en assistance mé dicale à la procré ation (AMP) [22,23]. De plus, l'utilisation de ces acides nuclé iques circulants peut é galement être envisagé e dans le cadre de l'infertilité masculine, afin de dé tecter de potentielles anomalies de la spermatogenè se [24][25][26][27][28][29].…”
Section: Introductionunclassified
“…De ré centes é tudes rapportent que l'expression de certains microARNs varient significativement dans le liquide folliculaire ou le sé rum de patientes souffrant d'un SOMPK [13,[15][16][17][18][19] ou d'une insuffisance ovarienne pré maturé e (IOP) [20,21]. Plusieurs microARNs, impliqué s dans les processus de folliculogenè se et sté roï-dogenè se, ont é té identifié s au niveau du follicule ovarien et notamment dans les cellules du cumulus [48][49][50] et de la granulosa [20,51,52].…”
Section: Introductionunclassified
See 1 more Smart Citation